2015
DOI: 10.1002/jps.24379
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization and In Vitro Biological Impact of Highly Aggregated Antibodies Separated into Size-Enriched Populations by Fluorescence-Activated Cell Sorting

Abstract: An IgG2 monoclonal antibody (mAb) solution was subjected to stirring, generating high concentrations of nanometer and subvisible particles, which were then successfully size enriched into different size bins by low speed centrifugation or a combination of gravitational sedimentation and Fluorescence-Activated Cell Sorting (FACS). The size-fractionated mAb particles were assessed for their ability to elicit the release of cytokines from a population of donor-derived human peripheral blood mononuclear cells (PBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 63 publications
3
53
3
Order By: Relevance
“…Again this latter result suggested differences in the mechanism of DC stimulation by Rituximab vs purified IgG1. Interleukin‐6, CCL2, CCL3 and CCL4 are part of the identified cytokine signature identified by Joubert et al, 25 using PBMCs and aggregated antibodies 37 . In this latter work, several cell subsets can contribute to cytokine and chemokine production that can explain some discrepancies with our results.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Again this latter result suggested differences in the mechanism of DC stimulation by Rituximab vs purified IgG1. Interleukin‐6, CCL2, CCL3 and CCL4 are part of the identified cytokine signature identified by Joubert et al, 25 using PBMCs and aggregated antibodies 37 . In this latter work, several cell subsets can contribute to cytokine and chemokine production that can explain some discrepancies with our results.…”
Section: Discussioncontrasting
confidence: 71%
“…In contrast, circular dichroïsm analysis was comparable for Rituximab and IgG1, showing a dramatic perturbation of the signal in relation with the tremendous increase in the light scattering after stirring. Previous structural studies on mAbs aggregates showed that the stirring stress indeed induced intramolecular loss of β‐sheet structures in IgG1 aggregates, whereas some intermolecular β‐sheet structures were detected 37 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, current available technology used to fractionate, purify, stabilize and deliver aggregates and particles in narrow, well-defined size ranges is limited. 67 Even when aggregates are fractionated, they may be unstable, and any changes in aggregate distributions that may occur upon administration are unknown. The reversibility/dissociability of aggregates under in vivo conditions could be important in this regard.…”
Section: Effects Of Product-related Factors On Immunogenicitymentioning
confidence: 99%
“…Protein pharmaceuticals can degrade via multiple chemical and physical processes, and detailed knowledge of these processes is critical to prevent degradation and to maintain stability of formulations . The last years have witnessed significant progress in our understanding of physical degradation processes, for example leading to aggregation and particle formation, in part due to the development of new analytical methodology and the critical evaluation of its potential and limitations . In contrast, the characterization of chemical degradation processes is far from complete, for the most part due to the continuous discovery of new reaction pathways and products, which can be unique to specific protein sequences.…”
Section: Introductionmentioning
confidence: 99%